PENGEMBANGAN MULTIMEDIA VIDEO PEMBELAJARAN DESAIN HIASAN MANIK-MANIK PADA BUSANA PESTA - Sefty Fadhilah; Mally Maeliah (Fesyen Perspektif, 2016)
This research was motivated by the media used in the process of learning design ornate beading on students in Program Studi Pendidikan Tata Busana, Universitas Pendidikan Indonesia. Presentation of learning material ornate designs of beads in a party dress would be easier if aided by multimedia instructional video with a clearer picture. The purpose of this study is developing multimedia instructional videos ornate designs of beads in a party dress. The research is the Research and Development. The research was conducted at Program Studi Pendidikan Tata Busana, Departemen Pendidikan Kesejahteraan Keluarga, Fakultas Pendidikan Teknologi dan Kejuruan, Universitas Pendidikan Indonesia. Based on the results of the verification and validation of subject matter experts and media experts conducted, showed that the result of the development of multimedia instructional videos ornate designs of beads in a party dress is feasible. This video multimedia improve the effectiveness of learning design ornate beading on a party dress to the value of the average percentage of the material aspects of 86.16%, 82.02% and media aspects by users get 90.62%. It can be concluded that the development of multimedia instructional videos ornate designs of beads can be applied and can be used in the learning process design of beads.